Síntese e atividade anti-trypanosoma de novos derivados nitroimidazol isoxazólicos com substituintes difenil éter e tioeter - LARISSA BIANCA BARBOSA DOS SANTOS (2023)
Chagas disease remains a significant public health problem, affecting 6-7 million people worldwide. The key issues with available therapeutic approaches include toxicity, a variety of adverse effects, and inefficiency in the chronic stage of the disease, emphasizing the need to find new drug treatments. Therefore, we synthesized seventeen novel 3,5-disubstituted isoxazole nitroimidazole analogs of benznidazole with diphenyl ether and thioether substituents and evaluated their antitrypanosomal activity and cytotoxicity. Compounds 13a-q were obtained in moderate to good yields (29–81%), 13a-g displayed greater activity than benznidazole. 13b (R1= Ph-O-(4-F-Ph)) and 13g (R1= Ph-O-(4-OCH3-Ph)) were the most active of all the synthesized compounds (IC50=0.50µM and IC50=0.64µM, respectively). Compounds 13h-n included 3-fluoro substituent in the first phenyl ring, resulting in lower activity and safety profile. The diphenyl thioether compounds 13o-q exhibited only moderate activity (IC50=11μM- 20.55μM). Further research is needed to better understand the role of diphenyl ether groups in antitrypanosomal activity.